Microstructure and mechanical properties of double-wire + arc additively manufactured Al-Cu-Mg alloys - Qi, Zewu; Cong, Baoqiang; Qi, Bojin; Sun, Hongye; Zhao, Gang; Ding, Jialuo (Elsevier, 2017)
As the properties of wire + arc additively manufactured Al-6.3Cu alloy cannot meet the applying requirements, a double-wire + arc additive manufacturing system was built to add magnesium into Al-Cu deposits for higher mechanical properties. Two commercial binary wires aluminum-copper ER2319 and aluminum-magnesium ER5087 were chosen as the filler metal to build Al-Cu-Mg components with different compositions by adjusting the wire feed speed. The microstructure and morphology of thin wall samples were characterized by optical micrographs (OM), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The Vickers hardness and tensile properties were investigated. The microstructure of Al-Cu-Mg deposits was mainly composed of coarse columnar grains and fine equiaxed grains with non-uniformly distributing characteristics. With higher Cu but lower Mg content, the strengthen phase turned to Al2Cu + Al2CuMg from Al2CuMg, and the micro hardness presented an increasing trend. The isotropic characteristics of ultimate tensile strength (UTS), yield strength (YS) and elongation were revealed in these samples. The UTS was about 280 ± 5 MPa both in horizontal and vertical directions for all samples. The YS showed an increasing trend from 156 MPa to 187 MPa with the same content trend, while elongation decreased from 8.2% to 6%. The fractographs exhibited typical brittle fracture characteristics.
Keywords: Mechanical properties; Double-wire + arc additive manufacturing; Al-Cu-Mg alloy; Microstructure